Multi-Mode Load-Limiting and Absorptive Ski Binding - Comden, Jonathan David; Regan, Sean Joseph; Roberti, Thomas Chi-Hang; Billington, Jacob J. (Worcester Polytechnic Institute, 2017)
This project aimed to design a ski binding that could reduce the risk of common injuries. In doing so, this project addressed the lack of displacement mechanisms in current ski bindings and the issue of inadvertent release. Through the use of axiomatic design, it was determined that in order to prevent these injuries, lateral and vertical response mechanisms at the toe and heel were required. Additionally, this allowed displacement to occur internally—rather than between boot and binding—reducing inadvertent release.